PEMBERDAYAAN EKONOMI BERBASIS MASJID(STUDI KRITIS PASAL 53, 54, DAN 55 PP. NOMOR14 TAHUN 2014 TENTANG PELAKSANAKAAN UU NOMOR 23 TAHUN 2011TENTANG PENGELOLAAN ZAKAT) - Supriyadi, Ahmad (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
History records that, at the time of  the Prophet Muhammad mosque plays animportant role in the development of  Islam. At that time the mosque not onlyas media ubuddiyah course, it is more vital role in education and empowermentof  Muslims organized and set in the mosque. That is: education, propaganda,social and economic. Birth of  law No. 23 of  2011 on the management of zakat provide an opportunity for the mosque to be the center of  economic empowerment of  the people. With a collector of  Zakat Unit (UPZ) Amil Zakat Nasional (BAZNAS,) the mosque will become points zakat collection,donation and sedekahyang collected from the congregation of  the mosque. Of the funds collected is used by the Collector Unit Manager Zakat (UPZ) ortakmir mosque to empower and improve the welfare of  the people.Keywords: Based Economic Empowerment Masjid, Zakat ManagementSejarah mencatat bahwa, pada masa Nabi Muhammad SAW masjid memainkan peran penting dalam perkembangan Islam. Pada saat itu masjidtidak hanya sebagai saja media yang ubuddiyah, lebih dari itu peran yang lebih penting yaitu dalam pendidikan dan pemberdayaan umat Islam terorganisirdan diatur dalam masjid. Peran tersebut yaitu pendidikan, propaganda, sosialdan ekonomi. Munculnya UU No. 23 Tahun 2011 tentang pengelolaanzakat memberikan kesempatan bagi masjid menjadi pusat pemberdayaanekonomi rakyat. Melalui Unit Pengumpul Zakat (UPZ) Amil ZakatNasional (BAZNAS,) masjid akan menjadi tempat pengumpulan zakat,sumbangan dan sedekah yang dikumpulkan dari jemaat masjid. Dari danayang terkumpul digunakan oleh Unit Pengumpul Zakat (UPZ) atau takmirmasjid untuk memberdayakan dan meningkatkan kesejahteraan rakyat.